Community participation in the development of libraries and children's rooms - Eduarte Salazar, José Pablo (2005)
Al referirse join the children's library, muchas times imagined un cuarto pequeño con muchos muñecos the cuddly, y algunos to libros y niños niñas. En realidad, this image is distant in both la verdad, pero una library room the Children that bad es eso, included, hasta en su nombre that it means.